2016
DOI: 10.1007/s12264-016-0074-1
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Epoxide Hydrolase Genetic Variant and Effectiveness of Nicotine Replacement Therapy in a Han Chinese Population

Abstract: Nicotine is a psychoactive alkaloid that is thought to play a key role in addiction to commercial tobacco products [1] and cotinine is its primary metabolite [2]. Pharmacological treatment, such as nicotine replacement therapy (NRT), is a valid solution to this problem. Tobacco smoke contains many carcinogens such as nitrosamines [i.e., nicotinederived nitrosamine ketone (NNK) and N-nitrosonornicotine (NNN)], and nicotine undergoes chemical conversion into NNK and NNN during the processes of curing and smoking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The long-lasting neuroplasticity changes induced by exposure to drugs of abuse are mediated by specific gene transcriptions [97]. Genetic analysis and functional studies have identified a wide range of candidate genes and their variants that regulate drug addiction, e.g., dopamine-related genes, glutamate-related genes, and transcription factors (e.g., the immediate early gene fosB) [97][98][99]. It has been shown that the development of addiction is positively associated with genetic factors, suggesting a high heritability feature of addiction [100].…”
Section: Therapeutic Gene Modulationmentioning
confidence: 99%
“…The long-lasting neuroplasticity changes induced by exposure to drugs of abuse are mediated by specific gene transcriptions [97]. Genetic analysis and functional studies have identified a wide range of candidate genes and their variants that regulate drug addiction, e.g., dopamine-related genes, glutamate-related genes, and transcription factors (e.g., the immediate early gene fosB) [97][98][99]. It has been shown that the development of addiction is positively associated with genetic factors, suggesting a high heritability feature of addiction [100].…”
Section: Therapeutic Gene Modulationmentioning
confidence: 99%
“…Wang et al [11] found that two singlenucleotide polymorphisms of microsomal epoxide hydrolase (rs1051740 and rs2234922) are involved in the processes of nicotine metabolism and abstinence. In addition, both polymorphisms are associated with the effectiveness of nicotine replacement therapy in a Chinese population.…”
mentioning
confidence: 99%